Faktor-faktor yang berhubungan dengan kejadian Kekurangan energi kronis (KEK) pada ibu hamil - Mitasari Mitasari; Juliastuti Juliastuti; Lia Lajuna; Yuni Sari; Iin Fitraniar (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: One of the nutritional problems among pregnant women is chronic energy deficiency (CED). CED is a condition in which pregnant women suffer from prolonged (chronic) inadequate food intake, resulting in various health problems. During pregnancy, women should meet their nutritional intake to prevent chronic energy deficiency. Purpose: This study aimed to determine the factors associated with the incidence of CED among pregnant women at Ingin Jaya Community Health Center, Aceh Besar, in 2025. Method: This research employed a quantitative approach with a descriptive-analytic design using a cross-sectional method. The study population consisted of all pregnant women with CED in the working area of Ingin Jaya Community Health Center, Ingin Jaya Subdistrict, Aceh Besar District, totaling 35 individuals. The sampling technique used was purposive sampling. Results: The findings showed that age (p = 0.038), knowledge (p = 0.049), and parity (p = 0.026) were significantly associated with chronic energy deficiency among pregnant women at Ingin Jaya Community Health Center, Aceh Besar. Conclusion: Factors associated with chronic energy deficiency among pregnant women at Ingin Jaya Community Health Center, Aceh Besar, were age, knowledge, and parity Suggestion: It is recommended that the community health center collaborate with community leaders to provide education to pregnant women regarding maternal nutrition during pregnancy and encourage the consumption of food and beverages with adequate nutritional value and calories to meet maternal nutritional needs and prevent chronic energy deficiency during pregnancy.